The perceptions of school administrators concerning "merit" concept: A metaphor study - Ramazan Gök (Journal of Pedagogical Research, 2020)
The aim of this study is to evaluate the perceptions of school principals and teachers about the concept of merit by means of metaphors. Metaphor has been used as a data collection method. The research data were obtained from 185 administrators working in public primary and secondary schools in five central districts of Antalya/Turkey. Easily accessible case sampling, one of the purposeful sampling methods, was used to determine the study group. The data were subjected to inductive content analysis by using metaphorical analysis. One hundred and nine metaphors produced by the participants were used in the analysis process. The findings show that the participants mostly likened the concept of merit to scale, tree, mother, ant, driving license, dress, ladder, car, and water. As a result, it is seen that the participants consider the concept of merit in the context of their hierarchical status and associate them with the features that managers should have. On the whole, school administrators explained the concept of merit in terms of suitability to the task, being capable, fair, indispensable, open to development, diligent, integrative, original and visionary, and being focused on career steps. In particular, it is important that competent managers are seen as people who give confidence to their environment, make the right decisions, and act as mentors. In addition, the perception of merit as a means of promotion in career steps is another important result of the study.